KEWENANGAN PENGURUS YAYASAN ATAS PERALIHAN HAK ATAS TANAH MILIK YAYASAN (Studi Kasus pada Yayasan Fakultas Pertanian Universitas Gadjah Mada) - Christ Aldo Susanto; M. Hudi Asrori Sayuti (Fakultas Hukum Universitas Sebelas Maret, 2021)
AbstractThis legal writing aims to find out how the formation of a foundation, the terms and responbilities of the foundation as a legal entity in Indonesia and to know what the duties and authorities off all organs, both mentors, managements and supervisors, especially in terms of the transfer of asset owned by foundations in Indonesia. This research is a descriptive legal research. The research method uses a qualitative approach. Legal materials that has been used is the primary legal materials and secondary legal materials. Mechanical collection of legal materials is carried out by the interviews and the study of literature. Development of the foundations in Indonesia has been very good, this is evidence by the existence of laws that have been ratified and must be adheard to by all components of the foundations in Indonesia. The foundations as a legal entity certainly has rules like other legal entities in Indonesia, including the transfer of assets owned by the foundation.The transition rules of the foundation’s assets which often cause many problems. This study will examine how the regulations on the transition of assets belonging to the foundation according to the law in force in Indonesia. AbstrakPenulisan hukum ini bertujuan untuk mengetahui bagaimana terbentuknya sebuah yayasan, syarat serta tanggung jawab yang dimiliki oleh yayasan sebagai badan hukum di Indonesia serta untuk mengetahui apa tugas dan wewenang dari seluruh organ baik itu pengurus, pembina dan pengawas terutama dalam hal peralihan aset milik yayasan di Indonesia. Penelitin ini merupakan penelitian hukum yang bersifat deskriptif. Penulisan hukum ini menggunakan pendekatan kualitatif. Bahan hukum yang digunakan adalah bahan hukum primer dan bahan hukum sekunder. Teknik pengumpulan bahan hukum yang dilakukan adalah dengan wawancara dan studi kepustakaan. Perkembangan yayasan di Indonesia sudah sangat baik, hal ini dibuktikan dengan adanya undang-undang yang telah disahkan dan harus ditaati oleh seluruh komponen yayasan di Indonesia. Yayasan sebagai sebuah badan hukum tentu memiliki aturan seperti badan hukum lain di Indonesia, termasuk tentang peralihan aset milik yayasan. Peraturan peralihan aset yayasan ini yang seringkali menimbulkan banyak masalah. Penelitian ini akan megkaji tentang bagaimana peraturan peralihan aset milik yayasan menurut undang-undang yang berlaku di Indonesia.